Cilia kinases in skeletal development and homeostasis. Issue 4 (18th October 2021) - Abraham, Sara P.; Nita, Alexandru; Krejci, Pavel; Bosakova, Michaela
Abstract: Primary cilia are dynamic compartments that regulate multiple aspects of cellular signaling. The production, maintenance, and function of cilia involve more than 1000 genes in mammals, and their mutations disrupt the ciliary signaling which manifests in a plethora of pathological conditions—the ciliopathies. Skeletal ciliopathies are genetic disorders affecting the development and homeostasis of the skeleton, and encompass a broad spectrum of pathologies ranging from isolated polydactyly to lethal syndromic dysplasias. The recent advances in forward genetics allowed for the identification of novel regulators of skeletogenesis, and revealed a growing list of ciliary proteins that are critical for signaling pathways implicated in bone physiology. Among these, a group of protein kinases involved in cilia assembly, maintenance, signaling, and disassembly has emerged. In this review, we summarize the functions of cilia kinases in skeletal development and disease, and discuss the available and upcoming treatment options. Key Findings: Primary cilia are cellular compartments with several critical functions during endochondral bone formation. For that reason, protein kinases that regulate formation or function of primary cilia also regulate skeletogenesis. Mutation in these cilia kinases produce a growing list of skeletal ciliopathies. In our review article, we summarize the functions of cilia kinases in skeletal development and disease, and discuss the available and upcoming treatment options.